THE EXPRESSION OF GEOPOLITICAL KNOWLEDGE IN THE WORKS “THE CITY OF VIRTUOUS PEOPLE” AND “INDIA” (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article examines the geopolitical knowledge in the work of Abu Nasir Farabi “The City of Virtuous people” and in the treatise of Abu Rayhan Beruni “India”. There was also a scientific analysis of geographical and geostrategic views expressed in the works, geopolitical knowledge on the development of the state, entry into international relations, reflections on the organization of a powerful state.